Business engineering incubators: a cooperation case for cluster’s development - Oliveira, Antônio Honorato De; Marins, Fernando Augusto Silva; Delamaro, Maurício César (Associação Brasileira de Engenharia de Produção, 2018)
AbstractPaper aimTo present the performance and contributions of a business incubator that acts as a link between the members of an industrial cluster and a higher education institution that acts in the field of engineering.OriginalityMost articles focus on incubators from the point of view of internal activities, the nature of incubation processes, and financing intermediary programs for nascent businesses. This work aimed to broaden the traditional approach of the academic constructs researched on the role of business incubators by bringing the contributions of one of the largest Brazilian business incubators to the formation and development of an industrial cluster.Research methodThe results represent the extract from a case study. The inductive method of basic research with a combined approach is applied for exploratory and descriptive purposes, using documentary analysis and field research.Main findingThis paper addresses a successful integration between an engineering school and the business environment through its incubator while summarizes the trajectory of this incubator, and highlights, among other contributions to the local industrial cluster, the significant survival rate of its graduated companies.Implications for theory and practiceCoordinated actions among members of the triple helix model are evidenced in this paper and may form the basis for similar experiments involving government agencies, educational institutions and the industrial environment.
Keywords: Triple helix model; Business engineering incubator; Clusters; Innovation; Development